2020
DOI: 10.1017/s0143814x20000185
|View full text |Cite
|
Sign up to set email alerts
|

Policy programme cycles through old and new programmatic groups

Abstract: This article draws on the Programmatic Action Framework (PAF) to tackle the question of how the dominance and decline of a specific policy programme in a policy sector can be explained. It starts from the observation that visionary policy programmes, defined as a set of policy goals and instruments that find their expression in subsequently adopted and interconnected policy reforms, may shape a sector’s policies over several decades. Linking policy programmes to programmatic groups that promote these programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Instead, elaborate methodological strategies for measuring preferences on the individual level have been introduced, as the quantitative (Weible et al 2004;Zafonte and Sabatier 2004) and qualitative (Litfin 2000) work on belief systems in ACF demonstrates. Moreover, as evidenced by the recently introduced "programmatic action framework" (Bandelow and Hornung 2020), preferences can also be rooted in shared biographies of policy elites. These insights call for a more systematic integration of actors-and advances in social network analyses may even enable quantitative researchers to include actors and coalitions more plainly in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, elaborate methodological strategies for measuring preferences on the individual level have been introduced, as the quantitative (Weible et al 2004;Zafonte and Sabatier 2004) and qualitative (Litfin 2000) work on belief systems in ACF demonstrates. Moreover, as evidenced by the recently introduced "programmatic action framework" (Bandelow and Hornung 2020), preferences can also be rooted in shared biographies of policy elites. These insights call for a more systematic integration of actors-and advances in social network analyses may even enable quantitative researchers to include actors and coalitions more plainly in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…The social identity approach itself emerged in Anglo-Saxon research (Haslam 2001 ; Hogg 2016 ). In public policy, it became a major tool of the Programmatic Action Framework (PAF), an approach that has its origins in French elite research (Bandelow and Hornung 2020 ; Hassenteufel et al. 2010 ; Hornung 2022 ).…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…At the same time, the creation of new institutions may help to implement policies and shield the new governance arrangements from alteration through other actors (Béland et al., 2020). This has been integrated in the PAF as a Program Institutionalization Hypothesis (Bandelow & Hornung, 2020).…”
Section: Programmatic Action and The Success Factors Of Policy Programsmentioning
confidence: 99%
“…Studies have identified the existence of programmatic groups in French defense policy (Faure, 2020; Genieys, 2010) and the health care systems of France, Germany, Spain, and the USA (Hassenteufel et al., 2010). While evidence confirms the occurrence of programmatic action in French and German health policy within a similar period of time alike (Genieys & Hassenteufel, 2015; Hornung & Bandelow, 2020), recent research shows that as opposed to France, the phase of programmatic action in German health policy seems to have ended (Bandelow & Hornung, 2020). The question is, what explains these divergent pathways of previously existent programmatic action in the two countries?…”
Section: Introductionmentioning
confidence: 97%